RESTITUSI DALAM MENANAMKAN DISIPLIN POSITIF PADA MURID - Mabruroh; Supriatna, Nana; Hasani, Aceng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to find out about the concept of restitution as a method for instilling positive discipline in students. Restitution is defined as a process that allows students to correct their mistakes and return to the group with stronger character. Emphasis is placed on the importance of personal growth through reflection, responsibility, and recovery, aimed at strengthening an individual's character and social relationships. With this approach, it is hoped that students can learn from their mistakes and become better emotionally, morally and socially. This article also underlines that making amends is not just about punishment, but rather a recovery process that supports the development of positive character in children. Through the application of positive culture in education, it is hoped that the character of the Pancasila student profile can be realized. Positive discipline is an approach to educating and guiding children that focuses on developing good behavior in a way that respects, supports and builds positive relationships, does not use punishment or threats to correct behavior, positive discipline aims to help children understand the consequences of their actions, learn from mistakes, and develop the social, emotional and moral skills necessary to become a responsible individual.